2019
DOI: 10.14569/ijacsa.2019.0100547
|View full text |Cite
|
Sign up to set email alerts
|

MHealth for Decision Making Support: A Case Study of EHealth in the Public Sector

Abstract: This paper seeks to explore factors that determine the acceptance of the MHealth application patients. The research relied on (UTAUT2) Unified Theory of Acceptance and Use of Technology to assess the level of acceptance of a new mobile health application by patients. The study involved conducting test surveys across medical hospitals in Jordan with the goal of collecting data from hospital visitors and their patients concerning their intention to use the new mobile health application. 98 questionnaires were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 16 publications
2
28
2
Order By: Relevance
“…Even though the smartphone is a popular device, capable of performing technology-based tasks, its use might not be welcome in a hospital. Authors in [9] confirmed that a mobile health application is generally accepted by the public to be integrated with the existing system of a hospital. Their study suggested eight factors that need to be considered when implementing mobile applications which were Hedonic Motivation, Performance, Expectancy, Social Influence, Effort Expectancy, Price Value, Habit, Facilitating Conditions, and Behavior.…”
Section: A Mobile Application In Health Carementioning
confidence: 82%
See 1 more Smart Citation
“…Even though the smartphone is a popular device, capable of performing technology-based tasks, its use might not be welcome in a hospital. Authors in [9] confirmed that a mobile health application is generally accepted by the public to be integrated with the existing system of a hospital. Their study suggested eight factors that need to be considered when implementing mobile applications which were Hedonic Motivation, Performance, Expectancy, Social Influence, Effort Expectancy, Price Value, Habit, Facilitating Conditions, and Behavior.…”
Section: A Mobile Application In Health Carementioning
confidence: 82%
“…Utilizing mobile applications for hospital management including the research to study the level of acceptance of mobile health applications [9] is an open research subject with many areas of interest [9][10][11][12][13][14]. Even though the smartphone is a popular device, capable of performing technology-based tasks, its use might not be welcome in a hospital.…”
Section: A Mobile Application In Health Carementioning
confidence: 99%
“…The first factor is Internet access behaviour that showed someone's health literacy. Other researchers found that Internet usage for health purposes is influenced by social influence (Al-Azzam et al, 2019;Duarte and Pinho, 2019), Internet facility access (Yuan et al, 2015;Al-Azzam et al, 2019;Duarte and Pinho, 2019), and motivation (Yuan et al, 2015). Furthermore, several studies have confirmed the significant impact of perceived Internet health information on Internet usage for health purposes (Lucassen and Schragen, 2013;Westerman et al, 2014;Lin et al, 2016;Kim et al, 2019).…”
Section: Previous Research and Research Gapmentioning
confidence: 94%
“…Based on UTAUT, Internet usage can be influenced by the Internet facility access (Venkatesh et al, 2012). Some researchers have revealed that Internet usage for health purposes is influenced by Internet facility access (Yuan et al, 2015;Al-Azzam et al, 2019;Duarte and Pinho, 2019). Given this, the fourth hypothesis of the study was formulated as follows.…”
Section: Facility Accessmentioning
confidence: 99%
See 1 more Smart Citation